Green Chemistry New Perspectives - Kumar, Brajesh; Debut, Alexis (IntechOpen, 2022)
Green Chemistry - New Perspectives is at the frontiers of this continuously evolving interdisciplinary science, and publishes research that attempts to reduce the environmental impact of the chemical enterprise by developing a technology base that is inherently non-toxic to living things and the environment. The book covers all aspects of green chemistry, including chemical synthesis, nano synthesis, eco-friendly processes, biomass, extraction techniques, environmental remediation, and energy, making it a unique reference resource. This will continue to encourage scientists around the world to develop novel synthetic methods or improve the existing ones to circumvent some of the problems and favours all aspects of green chemistry. This book is intended for academia, professionals, scientists, as well as graduate and undergraduate students without any geographical limitations.